The role of typology and proficiency in L2 processing of brazilian portuguese and english verbal morphology: an eye-movement study - Bandeira, Luana Alves (2015)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2015